MORALITY AND POLITICS WITH REFERENCE TO MACHIAVELLI’S THE PRINCE - Mohammed Seid Ali (European Scientific Journal, ESJ, 2015)
Niccolo Machiavelli (1469 -1527) was an Italian statesman and political writer. He was employed on diplomatic missions as a defense secretary for his nation. When he retired from his public life, he wrote one of his famous books, The Prince in 1513, which describes the mechanisms through which political power is gained and maintained. The prince is the most revolutionary work that opens a new chapter as far as the realm of modern political philosophy is concerned. Unlike the conventional understanding about political power during the ancient as well as medieval periods, Machiavelli’s political analysis does not associate the end of the state power to some extra- political (moral, religious and cultural) standards so that it has been defined as an end in itself. Accordingly, he confines his inquiries in to the means that are best suited to acquire, retain and expand political power. At the final analysis, he separates the discourse on political power as well as the means to acquire and sustain it from basic religious and conventional moral maxims. There is a white fact that the purpose of moral philosophy is to avoid evil and appreciate good acts through creating awareness in the minds of the society on what ought to /ought not to be done. In the prince, however, Machiavelli clearly reflects on how those evil acts from the standpoints of conventional morality and religion may not similarly be interpreted in the practical political or public lives of those who are in power. For him, the quest for political power is responded in effective and efficient manner when the prince knows the difference between private and public life and acts in accordance with ‘the reason of the state’. To sum up, the question of political power and the strategies to sustain it are the central issues which are to be correctly understood by any political personality. The question, how can a prince /a ruler acquire and sustain his political life with reference to his public and private morality, has been the theme of the paper. And, its departure has been developing a critical review of the writing of Machiavelli’s The Prince ,which reflects on the fundamental quest for those viable options of political power which may usually be indifferent to religious and moral guidelines. Accordingly, I have shown as to how much those good acts from the perspective of private religious and moral standards may not usually be working in the political lives of those who are in power. To this effect, different domestic and international experiences have been critically illustrated to substantiate the predominately Machiavellian nature of political leadership in the domestic as well as international arena. However, I have also tried to critically review and rebut Machiavelli’s ambitious quest for a pure, objective, descriptive and realistic analysis of political power which is free from relative sociocultural values and normative judgments.